On coregular closure operators - Gutierres, Gonçalo (1999)
Among closure operators in the sense of Dikranjan and Giuli [5] the regular ones have a relevant role and have been widely investigated. On the contrary, the coregular closure operators were introduced only recently in [3] and they need to be further investigated. In this paper we study co regular closure operators, in connection connectednesses and disconnectednesses, in the realm of topological spaces and modules.